2013
DOI: 10.1116/1.4798612
|View full text |Cite
|
Sign up to set email alerts
|

Study of hydrogen detection response time with Pt-gated diodes fabricated on AlGaN/GaN heterostructure

Abstract: Articles you may be interested inMethane detection using Pt-gated AlGaN/GaN high electron mobility transistor based Schottky diodes J. Vac. Sci. Technol. B 31, 032203 (2013); 10.1116/1.4803743 Effect of humidity on hydrogen sensitivity of Pt-gated AlGaN/GaN high electron mobility transistor based sensors AlGaN/GaN-based metal-oxide-semiconductor diode-based hydrogen gas sensorThe hydrogen detection response time of Pt-gated diode sensors fabricated on AlGaN/GaN heterostructure as a function of the hydrogen con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The increased current is attributed to the cleavage of S-H bond by noble metal, which is platinum in this device, resulting in the production of hydrogen atom or molecule. 15 Hydrogen molecule have been extensively demonstrated to be detected by Pt-coated Schottky diodes, 10,11 due to the dissociation of hydrogen molecule by platinum, resulting in hydrogen atoms, which cause the polarity change of the Pt/GaN interface, leading to the reduction of Schottky barrier. 16 The mechanism of hydrogen molecule detected by Pt-coated Schottky diodes is well studied and proved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased current is attributed to the cleavage of S-H bond by noble metal, which is platinum in this device, resulting in the production of hydrogen atom or molecule. 15 Hydrogen molecule have been extensively demonstrated to be detected by Pt-coated Schottky diodes, 10,11 due to the dissociation of hydrogen molecule by platinum, resulting in hydrogen atoms, which cause the polarity change of the Pt/GaN interface, leading to the reduction of Schottky barrier. 16 The mechanism of hydrogen molecule detected by Pt-coated Schottky diodes is well studied and proved.…”
Section: Resultsmentioning
confidence: 99%
“…Many of them have been studied for hydrogen detection. [9][10][11] Apart from the hydrogen detection, the Schottky diodes were also reported for detecting propane, 12 carbon monoxide, 13 acetylene (C 2 H 2 ), nitrous oxide (NO 2 ) 9 and ammonia (NH 3 ), 14 due to the good stability of GaN in high temperature and the high sensitivity of the GaN Schottky diodes. In this study, Pt/GaN Schottky is investigated for trace hydrogen sulfide detection in air as low as 0.1 ppm.…”
mentioning
confidence: 99%
“…at 800 °C under N2 ambient [19,20]. While most studies refer to H2 sensors [21][22][23], AlGaN/GaN sensors were also demonstrated for CO, CO2, NO, NO2, NH3, Cl, CH4, C2H2 [24][25][26][27][28][29][30]. Very few results of H2S detection with wide bandgap semiconductor devices have been reported so far.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…Hydrogen has been explored for conventional technologies such as hydrocracking of paraffin in petroleum refineries, fuel cells, internal combustion engines, power generation, etc. 6,7 For instance, in Refs. Thus, all hydrogen applications have safety issues requiring continuous and accurate monitoring for hydrogen leak during its transport, storage, and use.…”
Section: Introductionmentioning
confidence: 99%